Biodiversity conservation requires consideration of different life history stages - Yan-Fang Song; Xiao-Long Liu; Jia-Jia Liu; Qing-Qing Li; Xian-Qi Li; Wen-Zhu Lu; Wei-Wei Zhou; Zhi-Yong Yuan (Proceedings of the National Academy of Sciences, 2025)
Amid the biodiversity crisis, functional diversity, which is critical for ecosystem stability and conservation planning—faces challenges due to species’ complex life cycles. As the majority of animals, species with complex life histories may have distinct traits and ecological functions at different stages. Using all 557 Chinese anurans, we tested whether adult-based conservation protects entire taxa by analyzing functional trait diversity across life stages. We compiled adult and tadpole traits, mapped spatial diversity patterns, identified hotspots, recognized conservation priority species based on traits at different stages, and tested whether integrating information from different life history stages can effectively conserve functional diversity. Results showed functional diversity hotspots of adults and tadpoles are different. Species’ functional uniqueness between stages were not correlated, with only 18.8% species overlapped in conservation priority lists. Meanwhile, conservation strategies prioritizing species based on adult traits failed to protect tadpole functional diversity. The extent of functional diversity covered by these species was similar to that of randomly chosen species. These findings reject the hypothesis that conservation strategies made based on information of adults can adequately protect whole taxa. Nevertheless, when information from both stages is integrated, the conservation effectiveness has significantly improved. Thus, comprehensive biodiversity protection requires integrated assessments of all stages.